A transmission line model developed directly in phase domain - Souza, N. V. [UNESP]; Carvalho, C. G. [UNESP]; Kurokawa, S. [UNESP]; Pissolato, J. (Institute of Electrical and Electronics Engineers (IEEE), 2012)
The phases of a transmission line are tightly coupled due to mutual impedances and admittances of the line. One way to accomplish the calculations of currents and voltages in multi-phase lines consists in representing them in modal domain, where its n coupled phases are represented by their n propagation modes. The separation line in their modes of propagation is through the use of a modal transformation matrix whose columns are eigenvectors associated with the parameters of the line. Usually, this matrix is achieved through numerical methods which do not allow the achievement of an analytical model for line developed directly in the phases domain. This work will show an analytical model for phase currents and voltages of the line and results it will be applied to a hypothetical two-phase. It will be shown results obtained with that will be compared to results obtained using a classical model. © 2012 IEEE.
Keywords: Modal Domain; Newton-Raphson; Transformation matrix; Transmission line; Two-phase line; Classical model; Currents and voltages; In-phase; Modal domain; Modal transformation; Mutual impedance; Phase currents; Propagation mode; Tightly-coupled; Transformation matrices; Transmission line models; Analytical models; Electric lines; Transmission line theory; Linear transformations